United Kingdom-Anguilla-British Overseas Territory : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The downturn has accentuated strains on the financial system of Anguilla. The 2011 Article IV Consultation highlights that the growth outlook is improving with major tourism projects getting back on course, although a slow recovery is only expected to begin in 2012. Executive Directors have emphasized that a new fiscal framework is needed with an appropriate balance between current and capital expenditure and in line with the resources available. Fiscal policy should be designed to meet the combined objectives of debt sustainability, deficit reduction, and long-term economic growth.